Pengaruh Pemberian Kurma Sukkari Pada Ibu Bersalin Terhadap Durasi Persalinan - Firdausi, Nadya; Mukhlis, Hamid (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
The labor duration is closely related to complications of prolonged labor and bleeding, which are important issues that have not been resolved till now because it related to the Maternal Mortality Rate. One of the efforts that can be done to reduce the risk of mother in labor to the incidence of prolonged labor is by providing adequate nutrition as energy such as dates. The sugar content in dates is different from the sugar in other fruits such as sugar cane. Besides, the sugar in dates does not require a long process to be absorbed directly by the body. The purpose of this research was to prove the effect of giving sukkari dates to mothers in labor with the labor duration at the Hanifa Clinic in Raman Utara Sub-District East Lampung Regency in 2021. This research type is a quantitative study using a Quasi Experiment design with a Post Test Only Control Group Design approach. The population of this research were all mothers in labor normally at the Hanifa Clinic Raman Utara as many as 22 people, using a minimum sample of 17 respondents in the experimental group and 17 respondents in the control group that obtained from the Independent Practice of Midwives around the Hanifa Clinic location due to limited research time. The technique used is purposive sampling. The data analysis used univariate and bivariate analysis (independent t-test). The data analysis results showed that the average labor duration for respondents who were given Sukkari dates was 170.06 minutes and the average labor duration for respondents who were not given Sukkari dates was 270.88 minutes. It was found that there was an effect of giving Sukkari dates on the labor duration at the Hanifa Clinic, Raman Utara Sub-District, East Lampung Regency in 2021 (P-Value = 0.000 less than 0.05).